The negative correlation between testosterone levels and age in healthy Indonesian men residing in the special capital province of Jakarta, Indonesia - Parwanto, Mauritius Lambertus Edy (International Journal of Research in Medical Sciences, 2017)
Background: Testosterone levels in the circulation determined by production and secretion by Leydig cell in the testes. The action mechanism of testosterone to target cells mediated by sex hormone binding globulin (SHBG). The levels of testosterone and SHBG in circulation determine men’s health. The objective in this study to know the relationship between testosterone, SHBG and insulin with age in healthy Indonesian men residing in the special capital province of Jakarta, Indonesia. Methods: This study is a cross-sectional study involving 250 healthy Indonesian men residing in the special capital province of Jakarta, Indonesia. Consecutive sampling was done in this study. Testosterone, SHBG and insulin in the serum were measured by immunoradiometric assay (IRMA). Glucose, triglycerides and albumin were measured using a spectrophotometer. Regression analysis was done to know the correlation between testosterone, SHBG and insulin with age. Results: The levels of TT, free testosterone (FT), SHBG and percentage of free testosterone (%FT) in healthy Indonesian men were negatively correlated with age (p<0.05). Free testosterone index (FTI) and insulin are not correlated with age (p>0.05). The levels of SHBG, FT, %FT and FTI were correlated positively with TT (p<0.05), but insulin did not correlate with TT (p>0.05). The %FT and FTI were positively correlated with FT (p<0.05), but SHBG and insulin levels did not correlate with FT (p>0.05). SHBG levels are not correlated with insulin (p>0.05). The rate of decline in TT levels in this study 9.8% per decade, while in SHBG levels 8.19% per decade. Conclusions: The levels of TT, FT, % FT and SHBG in this study were negatively correlated with age, but the FTI and insulin did not correlate with age. The rate of decline in TT levels in this study 9.8% per decade, while in SHBG levels 8.19% per decade.